Domači odzivi na globalne izzive - Ciglič, Rok; Komac, Blaž; Logar, Erik; Zorn, Matija (Naravne nesreče, 2020)
The volume ('Domestic Responses to Global Challenges') contains fourteen chapters dealing with natural disasters. The chapters describe research findings and examples of the use of modern technologies in cases of natural disasters, with the focus on local responses to global challenges. The volume covers various topics such as earthquakes, draughts, heat waves, floods and avalanches, as well as responses and communication during natural disasters.